Ferritic stainless steel material for battery component, method for producing same, and battery component
By using ferrite system stainless steel that controls composition and precipitate amount, safety issues of battery components in terms of collision and thermal runaway are solved, and the efficient performance and low cost of the material are achieved.
Patent Information
- Application Number
- CN202380062299.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-26
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-25
AI Technical Summary
Existing battery component materials are prone to damage in collision accidents and have insufficient resistance to thermal runaway, resulting in safety hazards.
Ferrite system stainless steel material with controlled composition and specified precipitate amount is used to anneale and cool at a specific temperature by cold rolling materials to produce materials containing Ti- or Nb-based precipitates to improve impact absorption characteristics and high-temperature rigidity.
Improves the protection performance of battery components during collision and resistance to thermal runaway, reduces costs, and realizes lightweight material and efficient fuel economy.
Smart Images

Figure CN119895064A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a ferritic stainless steel material for battery components, a method for manufacturing the same, and a battery component. Specifically, the present invention relates to a ferritic stainless steel material used for battery components of transportation equipment, a method for manufacturing the same, and a battery component having the ferritic stainless steel material. Here, in this specification, the so-called "transportation equipment" means equipment for transporting goods or passengers such as automobiles, two-wheeled vehicles, three-wheeled vehicles, bicycles, buses, and railway vehicles. In addition, the so-called "battery component" means a component constituting a battery, such as a battery case, a battery pack, a battery module, a battery cover, etc. Background Art
[0002] In recent years, from the perspective of environmental issues, improving the fuel economy of conveying equipment has become a problem that must be faced. As one of the solutions, the lightweighting of the body of the conveying equipment is being actively promoted. The lightweighting of the body mostly depends on the lightweighting of the materials used in the parts constituting the body, such as reducing the thickness of the material. However, if the thickness of the material is reduced, the rigidity and collision absorption performance of the parts will be reduced. In this countermeasure, it is effective to increase the strength of the materials constituting the parts, and steel materials called high-strength ordinary steel (high-strength steel) are used.
[0003] However, since ordinary steel has low corrosion resistance, heavy painting becomes a prerequisite. Therefore, ordinary steel cannot be used for non-painted parts, lightly painted parts, or heavy painting leads to increased costs. In addition, ordinary steel also has low heat resistance, so it cannot withstand thermal runaway that sometimes occurs in battery components. Here, in this specification, the so-called "thermal runaway" means a state in which the heat inside the battery cannot be controlled for some reason, resulting in abnormal heat generation and fire depending on the situation.
[0004] On the other hand, stainless steel containing Cr has excellent corrosion resistance compared to ordinary steel, so it can be expected that the weight reduction and omission of painting brought about by the reduction of rust allowance (estimated thickness of rust) can be reduced. In addition, stainless steel also has excellent heat resistance compared to ordinary steel, so it has resistance to thermal runaway. Therefore, safety can be improved by suppressing fire and the spread of fire. Therefore, by using stainless steel, the advantages of improved fuel economy, simplified painting, and improved safety brought about by lightweighting of the vehicle body become greater.
[0005] In transportation equipment, automobiles and other fields, the diversification of powertrains is also advancing. In addition to internal combustion engine vehicles, diesel vehicles and hybrid vehicles, electric vehicles and fuel cell vehicles without internal combustion engines are also being put into practical use. In particular, electric vehicles are equipped with large-capacity batteries and driven by electric motors, and are equipped with multiple battery components. Since multiple batteries are installed in electric vehicles, when one battery has thermal runaway, other batteries are also prone to cause thermal runaway in a chain reaction, and depending on the situation, there is a risk of causing a vehicle fire.
[0006] As materials used for battery components, stainless steel, aluminum, resin, Ni-plated steel, and the like are used.
[0007] For example, as a stainless steel material for battery components, Patent Document 1 discloses a method for manufacturing a lithium-ion secondary battery housing using an austenitic stainless steel foil as a raw material. In addition, Patent Document 2 discloses the use of an austenitic stainless steel sheet for a battery housing for electric vehicles having excellent heat resistance. In addition, Patent Document 3 discloses a ferritic stainless steel to which 16.0 to 32.0 mass% of Cr is added as an electrode material and an electrode housing for a large-capacity battery.
[0008] However, the stainless steel materials disclosed in Patent Documents 1 to 3 do not have sufficient impact absorption properties (impact resistance) when used for battery components. Therefore, when an impact is applied to the battery due to a collision accident or the like, the battery is damaged, a short circuit occurs in the battery, and thermal runaway is easily caused.
[0009] On the other hand, as a technology for suppressing thermal runaway of a battery caused by impact, a technology for providing an insulating layer on a laminated seal constituting a case for a secondary battery is proposed in Patent Document 4. In addition, Patent Documents 5 to 7 also propose technologies for suppressing thermal runaway of a battery by providing a member formed of mica on a battery component.
[0010] However, these technologies have the problem that they cannot prevent damage to battery components, and the cost increases due to the provision of insulating layers and mica. In addition, these technologies do not improve the impact absorption properties of stainless steel materials, and therefore it is difficult to reduce the thickness of battery components.
[0011] Prior Art Literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent No. 6090923
[0014] Patent Document 2: Japanese Patent Application Laid-Open No. 10-188922
[0015] Patent Document 3: Japanese Patent Application Publication No. 2009-167486
[0016] Patent Document 4: Japanese Patent No. 6522736
[0017] Patent Document 5: Japanese Patent Application No. 2022-522369
[0018] Patent Document 6: International Publication No. 2019 / 150771
[0019] Patent Document 7: Japanese Patent No. 6631726 Summary of the invention
[0020] As described above, there is no material that protects the battery when an impact is applied to the battery due to a collision accident or the like and has excellent resistance to thermal runaway.
[0021] Under such circumstances, an object of the present invention is to provide a ferritic stainless steel material for battery components, which has excellent battery protection performance and resistance to thermal runaway when an impact is applied to the battery due to a collision accident or the like, and a method for producing the same, as well as a battery component.
[0022] As a result of intensive research, the present inventors have found that a ferritic stainless steel material having controlled composition and the amount of predetermined precipitates can solve the above-mentioned problems. In addition, the present inventors have found that a ferritic stainless steel material having such characteristics can be obtained by annealing a cold-rolled material having a predetermined composition under specific conditions and cooling the material. The present invention has been completed based on these findings.
[0023] That is, the present invention relates to a ferritic stainless steel material for battery components, which has the following composition: containing, by mass, 0.001 to 0.050% C, 0.01 to 2.00% Si, 0.01 to 2.00% Mn, 0.010 to 0.050% P, 0.0001 to 0.0100% S, 10.0 to 30.0% Cr, 0.001 to 0.050% N, and further containing one or two selected from 0.01 to 0.50% Ti and 0.01 to 0.60% Nb, with the balance being Fe and impurities,
[0024] It contains 0.010 volume % or more of Ti-based precipitates and / or Nb-based precipitates.
[0025] The present invention also relates to a method for producing a ferritic stainless steel material for battery components, wherein a cold-rolled material is annealed at a temperature of 850 to 1050°C and then cooled at a cooling rate of 10°C / second or less to 800°C, wherein the cold-rolled material has a composition comprising, on a mass basis, 0.001 to 0.050% C, 0.01 to 2.00% Si, 0.01 to 2.00% Mn, 0.010 to 0.050% P, 0.0001 to 0.0100% S, 10.0 to 30.0% Cr, 0.001 to 0.050% N, and further contains one or two selected from 0.01 to 0.50% Ti and 0.01 to 0.60% Nb, with the balance being Fe and impurities.
[0026] Furthermore, the present invention relates to a battery component including a ferritic stainless steel material for a battery component.
[0027] According to the present invention, a ferritic stainless steel material for battery components, which is excellent in battery protection performance and resistance to thermal runaway when an impact is applied to the battery due to a collision accident or the like, a method for producing the same, and a battery component can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The ferritic stainless steel material containing 0.010 volume % of Ti-based precipitates and / or Nb-based precipitates and the ferritic stainless steel material containing no Ti-based precipitates and / or Nb-based precipitates are expressed as 10 3 A graph showing the relationship between strain and flow stress when a tensile test is performed at a strain rate of 1 / s. DETAILED DESCRIPTION
[0029] In order to ensure the protection performance of the battery when an impact is applied to the battery due to a collision accident, etc., it is necessary to improve the impact absorption characteristics (impact resistance) of the ferritic stainless steel material used as the material of the battery components during high-speed deformation. In addition, in order to ensure resistance to thermal runaway, it is necessary to improve the high-temperature rigidity of the ferritic stainless steel material.
[0030] In the present invention, as an evaluation of the impact absorption characteristics during high-speed deformation, an impact caused by a collision accident or the like is assumed, and a 10 3 The flow stress at 10% strain during a tensile test at a strain rate of / sec, and the Young's modulus at 900°C were used as an evaluation of high temperature rigidity, and various ferritic stainless steel materials were prepared and analyzed and studied in detail. As a result, it was found that the impact absorption characteristics during high-speed deformation and high-temperature rigidity can be improved by controlling the composition of the ferritic stainless steel material and the amount of a predetermined precipitate, thereby completing the present invention.
[0031] The following is a specific description of the embodiments of the present invention based on the above viewpoints. It should be understood that the present invention is not limited to the following embodiments, and that embodiments obtained by appropriately applying changes, improvements, etc. to the following embodiments without departing from the gist of the present invention based on the common knowledge of those skilled in the art also fall within the scope of the present invention.
[0032] In addition, in this specification, "%" about a component means "mass %" unless otherwise specified.
[0033] (1) Ferritic stainless steel for battery components
[0034] The ferritic stainless steel material for battery components according to an embodiment of the present invention (hereinafter sometimes referred to as "ferritic stainless steel material") has the following composition: contains C: 0.001-0.050%, Si: 0.01-2.00%, Mn: 0.01-2.00%, P: 0.010-0.050%, S: 0.0001-0.0100%, Cr: 10.0-30.0%, N: 0.001-0.050%, further contains one or two selected from Ti: 0.01-0.50% and Nb: 0.01-0.60%, and the balance is Fe and impurities.
[0035] Here, in this specification, the so-called "impurities" means: components that are mixed in the industrial production of ferritic stainless steel materials due to various factors such as raw materials such as ores and wastes and the production process, and are allowed within the range that does not cause adverse effects on the present invention. For example, impurities also include unavoidable impurities. Examples of impurities include O, As, Pb, etc. It is preferable to reduce impurities as much as possible.
[0036] In addition, in this specification, the so-called "stainless steel material" means a material formed of stainless steel, and the material form is not particularly limited. Examples of the material form include plate (including strip), rod, tube, etc. In addition, various steel sections with cross-sectional shapes such as T-shaped and I-shaped can be used.
[0037] Moreover, in this specification, the so-called "ferritic system" means that the metal structure is mainly ferrite phase at room temperature. Therefore, the "ferritic system" also includes the situation that a small amount of phases other than the ferrite phase (such as austenite phase, martensite phase, etc.) are contained. However, the "ferritic system" does not include: a complex structure of ferrite phase and austenite phase, a complex structure of ferrite phase and martensite phase, and a complex structure of ferrite phase, austenite phase and martensite phase. Stainless steel materials with these complex structures have high strength, but the impact absorption characteristics (flow stress during high-speed deformation) and processability during high-speed deformation are insufficient.
[0038] The ferritic stainless steel material according to the embodiment of the present invention may further contain Ni: 0.01-2.00%, Al: 0.001-1.000%, Cu: 0.01-2.00%, Mo: 0.01-3.00%, V: 0.01-0.50%, Zr: 0.01-0.50%, B: 0.0002-0.0050%, Ca: 0.0005-0.0100%, W: 0.10-3 .00%, Sn: 0.01~0.50%, Co: 0.03~0.30%, Mg: 0.0002~0.0100%, Sb: 0.005~0.300%, REM: 0.002~0.200%, Ga: 0.0002~0.3000%, Ta: 0.001~1.000%, Hf: 0.001~1.000%, Bi: 0.001~0.020% or more.
[0039] Each component is described in detail below.
[0040] <C: 0.001~0.050%>
[0041] C is an element that reduces corrosion resistance and heat resistance, so the C content is set to 0.050% or less. However, excessive reduction of C will lead to an increase in refining costs, so the lower limit of the C content is set to 0.001%. In addition, from the perspective of impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation), the lower limit of the C content is preferably 0.003% or more. In addition, from the perspective of weldability, the upper limit of the C content is preferably 0.010% or less. Furthermore, if manufacturability and processability are taken into consideration, the C content is more preferably 0.003 to 0.008%.
[0042] <Si: 0.01~2.00%>
[0043] Si is a deoxidizing element. In addition, Si is a solid solution strengthening element and is an element effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation), so the Si content is set to 0.01% or more. However, excessive addition of Si will lead to a sharp decrease in ductility, so the upper limit of the Si content is set to 2.00%. In addition, considering corrosion resistance and manufacturability, the Si content is preferably 0.05 to 0.90%. Furthermore, considering weldability and toughness, the Si content is more preferably 0.10 to 0.40%.
[0044] <Mn: 0.01~2.00%>
[0045] Mn is a deoxidizing element. In addition, Mn is a solid solution strengthening element and is an element effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation), so the Mn content is set to 0.01% or more. However, excessive addition of Mn will lead to a decrease in corrosion resistance, so the upper limit of the Mn content is set to 2.00%. In addition, considering oxidation resistance and strength, the Mn content is preferably 0.10 to 1.00%. Furthermore, considering manufacturability and weldability, the Mn content is more preferably 0.20 to 0.50%.
[0046] <P: 0.010~0.050%>
[0047] P reduces processability, corrosion resistance, and manufacturability, so the less the better. When the P content is too much, coarse phosphides are generated, which become the starting point for void generation during high-speed deformation, so the upper limit of the P content is set to 0.050%. On the other hand, the formation of fine FeTiP and FeNbP will improve the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation), so the lower limit of the P content is set to 0.010%. In addition, considering the refining cost and processability, the P content is preferably 0.020-0.030%.
[0048] <S: 0.0001~0.0100%>
[0049] S reduces processability, corrosion resistance, and manufacturability, so the less the better. If the S content is too high, coarse sulfides are generated, which become the starting point for void generation during high-speed deformation, so the upper limit of the S content is set to 0.0100%. On the other hand, the formation of fine TiS and Ti4C2S2 will improve the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation), so the lower limit of the S content is set to 0.0001%. In addition, considering the refining cost and weldability, the S content is preferably 0.0005-0.0020%.
[0050] <Cr: 10.0~30.0%>
[0051] Cr is an element added to improve corrosion resistance and heat resistance. In particular, in order to omit painting and improve high temperature rigidity, the Cr content is set to 10.0% or more. On the other hand, if the Cr content is too much, the toughness is significantly reduced, so the upper limit of the Cr content is set to 30.0%. In addition, considering the manufacturability, cost, corrosion resistance of the welded part, and impact absorption characteristics during high-speed deformation, the Cr content is preferably 11.0 to 18.0%.
[0052] <N: 0.001~0.050%>
[0053] N is an element that reduces corrosion resistance and heat resistance, so the N content is set to 0.050% or less. However, excessive reduction of N will lead to an increase in refining costs, so the lower limit of the N content is set to 0.001%. In addition, from the perspective of impact absorption characteristics during high-speed deformation, the lower limit of the N content is preferably 0.003% or more. In addition, from the perspective of weldability, the upper limit of the N content is preferably 0.010% or less. Furthermore, considering manufacturability and processability, the N content is more preferably 0.003 to 0.008%.
[0054] <One or two selected from Ti: 0.01 to 0.50% and Nb: 0.01 to 0.60%>
[0055] Ti and Nb, combined with C and N, inhibit the formation of coarse Cr carbonitrides, thereby preventing intergranular corrosion, and promote the development of {111} texture, which helps to improve workability (such as deep drawability). In addition, Ti and Nb are also elements required to generate Ti-based precipitates and Nb-based precipitates that are effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation). Here, in this specification, the so-called "Ti-based precipitates and Nb-based precipitates" mean phosphides (FeTiP, FeNbP) and sulfides (TiS, Ti4C2S2) in addition to carbides and nitrides of Ti and Nb. In order to generate a specified amount of Ti-based precipitates and Nb-based precipitates in ferritic stainless steel, the Ti content is set to 0.01% or more, and the Nb content is set to 0.01% or more. However, excessive addition of Ti and Nb will make the Ti-based precipitates and Nb-based precipitates too coarse, thereby reducing toughness. Therefore, the upper limit of the Ti content is set to 0.50%, and the upper limit of the Nb content is set to 0.60%. In addition, from the viewpoints of processability, manufacturability and cost, the Ti content and the Nb content are preferably 0.05 to 0.30%. Furthermore, from the viewpoint of manufacturing cost, the Ti content and the Nb content are more preferably 0.05 to 0.20%.
[0056] <Ni: 0.01~2.00%>
[0057] Ni is an element that contributes to high strength and is effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation). More than 0.01% is added as needed. However, excessive addition of Ni will cause a decrease in high-temperature rigidity (high-temperature Young's modulus), an increase in component cost, the formation of austenite phase and martensite phase, and reduce formability, so the upper limit of the Ni content is set to 2.00%. In addition, if toughness and corrosion resistance are considered, the Ni content is preferably 0.10-1.00%. Furthermore, if heat resistance is considered, the Ni content is more preferably 0.20-0.50%.
[0058] <Al: 0.001~1.000%>
[0059] Al is an element added as a deoxidizing element. In order to efficiently realize this effect, 0.001% or more is added as needed. In addition, Al is an element that is also effective in improving the processability brought about by the formation of nitrides, the high strength brought about by solid solution strengthening, and the improvement of oxidation resistance. However, excessive addition of Al will lead to a decrease in high temperature rigidity, the generation of surface defects, a decrease in weldability, and a decrease in ductility caused by coarse AlN. Therefore, the upper limit of the Al content is set to 1.000%. In addition, if the deoxidation efficiency and toughness are considered, the Al content is preferably 0.020-0.500%. Furthermore, if weldability is considered, the Al content is more preferably 0.020% or more and less than 0.100%.
[0060] <Cu: 0.01~2.00%>
[0061] Cu contributes to the improvement of corrosion resistance, the improvement of high temperature rigidity and high temperature strength brought about by the precipitation of ε-Cu, so 0.01% or more is added as needed. However, if the Cu content is too much, the ductility is significantly reduced, so the upper limit of the Cu content is set to 2.00%. In addition, considering oxidation resistance and component cost, the Cu content is preferably 0.05-1.50%. Furthermore, considering toughness and weldability, the Cu content is more preferably 0.10-0.50%.
[0062] <Mo: 0.01~3.00%>
[0063] Mo is an element that improves corrosion resistance. In addition, Mo is a solid solution strengthening element, which is effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation). Therefore, Mo is added at 0.01% or more as needed. However, excessive addition of Mo not only reduces processability and increases costs, but also significantly reduces toughness, so the upper limit of the Mo content is set to 3.00%. In addition, from the viewpoint of high-temperature rigidity and oxidation resistance, the Mo content is preferably 0.10 to 1.50%. Furthermore, from the viewpoint of reducing costs, the Mo content is more preferably 0.10 to 1.20%.
[0064] <V: 0.01~0.50%, Zr: 0.01~0.50%>
[0065] V and Zr, like Ti and Nb, are elements that combine with C and N to suppress the formation of coarse Cr carbonitrides. In addition, V and Zr are also effective elements for the formation of fine precipitates (Zr(C, N), V(C, N)) for improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation). Therefore, V and Zr are each added by 0.01% or more as needed. However, excessive addition of V and Zr will cause a decrease in toughness and a decrease in high-temperature rigidity, so the upper limits of the V content and the Zr content are both set to 0.50%. In addition, from the viewpoint of formability, the V content and the Zr content are preferably 0.05-0.30%. Furthermore, if the impact absorption characteristics and bendability of the weld during high-speed deformation are taken into consideration, the V content and the Zr content are more preferably 0.1-0.2%.
[0066] <B: 0.0002~0.0050%>
[0067] In addition to being an element effective for high strength, B is also an element that suppresses secondary processing cracks. In addition, B forms borides, which are effective in improving the impact absorption characteristics during high-speed deformation (flow stress during high-speed deformation). Therefore, B is added as needed by 0.0002% or more. However, excessive addition of B will become the starting point for void formation, and the formability and toughness will decrease, so the upper limit of the B content is set to 0.0050%. In addition, if corrosion resistance is considered, the B content is preferably 0.0002-0.0020%. Furthermore, if weldability is considered, the B content is more preferably 0.0005-0.0010%.
[0068] <Ca: 0.0005~0.0100%>
[0069] Ca fixes S and improves hot workability, so 0.0005% or more is added as needed. On the other hand, excessive addition of Ca not only reduces corrosion resistance, but also reduces ductility during high-speed deformation due to coarse CaS. Therefore, the upper limit of the Ca content is set to 0.0100%. In addition, from the viewpoint of manufacturability, the Ca content is preferably 0.0005-0.0010%.
[0070] <W:0.10~3.00%>
[0071] W is an element that improves corrosion resistance and is also a solid solution strengthening element. Therefore, 0.10% or more is added according to the corrosion resistance level based on the use environment. However, excessive addition of W will lead to reduced workability and toughness and increased costs, so the upper limit of the W content is set to 3.00%. The W content is preferably 0.10 to 1.50%.
[0072] <Sn: 0.01~0.50%>
[0073] Sn contributes to the improvement of corrosion resistance and high temperature strength, so 0.01% or more is added as needed. However, excessive addition of Sn sometimes causes slab cracks during manufacturing, and grain boundary cracks during processing (such as hole expansion) also become significant. Therefore, the upper limit of the Sn content is set to 0.50%. Furthermore, considering the refining cost and manufacturability, the Sn content is preferably 0.01-0.30%.
[0074] <Co: 0.03~0.30%>
[0075] Co contributes to the improvement of high temperature strength, so 0.03% or more is added as needed. However, excessive addition of Co will lead to reduced toughness during manufacturing, increased costs, and reduced processability (such as hole expansion). Therefore, the upper limit of the Co content is set to 0.30%. Furthermore, considering the refining cost and manufacturability, the Co content is preferably 0.03-0.10%.
[0076] <Mg: 0.0002~0.0100%>
[0077] Mg is an element added as a deoxidizing element. In addition, Mg contributes to the improvement of manufacturability due to the refinement of ferrite grains, the improvement of surface defects called ridges, and the improvement of the workability of welds. In order to obtain these effects, the Mg content is set to 0.0002% or more. However, excessive addition of Mg not only significantly reduces corrosion resistance, but also reduces workability (such as hole expansion) due to coarse MgO. Therefore, the upper limit of the Mg content is set to 0.0100%. Considering manufacturability, the Mg content is preferably 0.0002 to 0.0020%.
[0078] <Sb: 0.005~0.300%>
[0079] Sb is an element that segregates at grain boundaries and thus has the effect of improving high temperature strength. In order to obtain the effect of Sb addition, the Sb content is set to 0.005% or more. However, excessive addition of Sb may cause grain boundary cracks during processing (such as hole expansion) and cracks during welding due to Sb segregation, so the upper limit of the Sb content is set to 0.300%. Considering high temperature characteristics, manufacturing costs and toughness, the Sb content is preferably 0.030-0.200%, and more preferably 0.050-0.100%.
[0080] <REM: 0.002~0.200%>
[0081] REM (rare earth element) is effective in improving oxidation resistance, and is added at 0.002% or more as needed. However, even if REM is added excessively, the effect is saturated, and the corrosion resistance and hole expansion properties are reduced due to REM granulation, so the upper limit of the REM content is set to 0.200%. Considering processability and manufacturing cost, the REM content is preferably 0.002 to 0.100%.
[0082] REM follows a general definition. That is, REM is a general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). REM can be added alone or in the form of a mixture.
[0083] <Ga: 0.0002~0.3000%>
[0084] Ga is an element added as needed to improve corrosion resistance and suppress hydrogen embrittlement. In particular, from the viewpoint of the formation of sulfides and hydrides that are effective in obtaining these effects, the lower limit of the Ga content is set to 0.0002%. In addition, from the viewpoint of manufacturability and cost, the Ga content is preferably 0.0020% or more. However, excessive addition of Ga may cause the formation of coarse sulfides and thus reduce workability (such as hole expansion), so the upper limit of the Ga content is set to 0.3000%.
[0085] <Ta: 0.001~1.000%, Hf: 0.001~1.000%>
[0086] Ta and Hf are elements effective in improving high temperature strength and are added as needed. To achieve such an effect, the Ta content and the Hf content are both set to 0.001-1.000%. From the viewpoint of improving high temperature strength, the Ta content and the Hf content are preferably 0.100% or less, and more preferably 0.010% or less.
[0087] <Bi: 0.001~0.020%>
[0088] Bi is an element effective in improving machinability and is added as needed. To obtain such an effect, the Bi content is set to 0.001 to 0.020%. From the viewpoint of improving machinability, the Bi content is preferably 0.015% or less.
[0089] The ferritic stainless steel material of the embodiment of the present invention contains 0.010 volume % or more of Ti-based precipitates and / or Nb-based precipitates. That is, the ferritic stainless steel material of the embodiment of the present invention may be a Ti-based precipitate of 0.010 volume % or more, a Nb-based precipitate of 0.010 volume % or more, or a total amount of Ti-based precipitates and Nb-based precipitates of 0.010 volume % or more. By controlling the amount of Ti-based precipitates and / or Nb-based precipitates within such a range, the impact absorption characteristics and high temperature rigidity during high-speed deformation can be improved. On the other hand, the upper limit of the amount of Ti-based precipitates and / or Nb-based precipitates is not particularly limited, but when too much, sometimes poor forming is caused by the formation of voids. From the viewpoint of suppressing this problem, the amount of Ti-based precipitates and / or Nb-based precipitates is preferably 0.200 volume % or less. In addition, considering low-temperature toughness and weldability, the amount of Ti-based precipitates and / or Nb-based precipitates is more preferably 0.020 to 0.100% by volume.
[0090] The amount of Ti-based precipitates and / or Nb-based precipitates in the ferritic stainless steel material can be determined from the area ratio of the region where the Ti-based precipitates and / or Nb-based precipitates exist in the entire structure by microscopic observation of a cross section of the ferritic stainless steel material according to the point method specified in JIS G0555:2003.
[0091] The particle size of the Ti-based precipitate and / or the Nb-based precipitate is not particularly limited, but is preferably 10 μm or less, more preferably 9 μm or less. By controlling the particle size of the Ti-based precipitate and / or the Nb-based precipitate within this range, in addition to improving the impact absorption characteristics and high temperature rigidity during high-speed deformation, it is also possible to suppress the formation of voids during forming processing and thus improve corrosion resistance. Furthermore, the lower limit of the particle size of the Ti-based precipitate and / or the Nb-based precipitate is not particularly limited, but is typically 0.1 μm, preferably 1 μm.
[0092] The particle size of the Ti-based precipitate and / or the Nb-based precipitate can be measured by observing the cross section of the ferritic stainless steel material using a scanning electron microscope. In addition, the particle size of the Ti-based precipitate and / or the Nb-based precipitate is obtained as the diameter of an equivalent circle (equivalent circle diameter) equal to its area.
[0093] The ferritic stainless steel material according to the embodiment of the present invention is 10 3 The flow stress at 10% strain in a tensile test performed at a strain rate of 1 / s is preferably 500 MPa or more.
[0094] Here, 10 3The flow stress at 10% strain during a tensile test at a strain rate of 100 / second is an indicator of the impact absorption characteristics during high-speed deformation assuming an impact caused by a collision accident or the like. If the flow stress is 500MPa or more, it can be said that the impact absorption characteristics during high-speed deformation are excellent, and it is a level that can ensure the collision safety of battery components of general automobiles. If the lightweighting caused by the reduction in thickness of the battery components composed of ferritic stainless steel is taken into account, the flow stress is more preferably 550MPa or more, and more preferably 600MPa or more.
[0095] Here, as an example, a ferritic stainless steel material containing 0.010 volume % of Ti-based precipitates and / or Nb-based precipitates (denoted as "Inventive Example") and a ferritic stainless steel material containing no Ti-based precipitates and / or Nb-based precipitates (denoted as "Comparative Example") were measured at 10 3 The results of the tensile test at a strain rate of / s are shown in Figure 1 . Figure 1 It is a graph showing the relationship between strain (x-axis) and flow stress (y-axis). Note that the ferritic stainless steel materials of the invention examples and comparative examples all had a composition containing 17% Cr-0.01% C-0.01% N.
[0096] like Figure 1 As shown in the figure, the flow stress of the invention example at 10% strain is as high as 500 MPa or more, and the impact absorption property at high-speed deformation is excellent. In contrast, the flow stress of the comparative example at 10% strain is less than 500 MPa. This shows that in the case of a collision accident with a strain rate of 10 3 When the flow stress is extremely high, the presence of Ti-based precipitates and / or Nb-based precipitates effectively inhibits the movement of dislocations, leading to an increase in flow stress.
[0097] The ferritic stainless steel material according to the embodiment of the present invention preferably has a Young's modulus at 900° C. of 80 GPa or more.
[0098] Here, the Young's modulus at 900°C is an indicator of high-temperature rigidity. In the event of a collision accident or the like, the interior of the damaged battery will instantly reach a high temperature of about 900°C, so other battery components constituting the battery are also exposed to high temperatures. At this time, if the Young's modulus at 900°C is less than 80GPa, the battery components are deformed and easily develop into thermal runaway. In contrast, if the Young's modulus at 900°C is above 80GPa, the deformation of the battery components can be suppressed and thermal runaway can be suppressed. If the lightweighting caused by the reduction in the thickness of the battery components composed of ferritic stainless steel is considered, the Young's modulus at 900°C is more preferably above 90GPa. Furthermore, it can be said that the higher the Young's modulus at 900°C, the better the high-temperature rigidity, so its upper limit is not particularly limited, for example, 200GPa, generally 150GPa.
[0099] The Young's modulus at 900° C. can be determined by a resonance method in accordance with the method specified in JIS Z2280:1993.
[0100] The ferritic stainless steel material according to the embodiment of the present invention preferably has a breaking elongation of 30% or more at room temperature (25°C).
[0101] Here, the elongation at break at room temperature is an indicator of processability. By setting the elongation at break at room temperature to 30% or more, processability of battery components having various shapes can be ensured. The upper limit of the elongation at break at room temperature is not particularly limited, but is, for example, 50%.
[0102] The elongation at break at room temperature can be determined by conducting a tensile test in accordance with JIS Z2241:2011 using a JIS No. 13 B test piece produced so that the rolling direction of the ferritic stainless steel material is parallel to the parallel portion.
[0103] The ferritic stainless steel material according to the embodiment of the present invention preferably has a maximum pitting depth of less than 200 μm.
[0104] Here, the maximum pitting depth is an index showing corrosion resistance. When the maximum pitting depth is less than 200 μm, it can be said that the corrosion resistance is excellent.
[0105] The maximum pitting depth can be determined by subjecting the ferritic stainless steel material to 30 cycles of the JASO-CCT test and rust removal treatment, and then measuring the material by a depth of focus method using a microscope.
[0106] The thickness of the ferritic stainless steel material of the embodiment of the present invention can be appropriately set according to the characteristics of the product using the ferritic stainless steel material, etc., and is not particularly limited. For example, if the lightweight of the ferritic stainless steel material and the battery components formed using the ferritic stainless steel material is considered, the thickness of the ferritic stainless steel material is preferably less than 1.0 mm. In addition, if the rigidity of the ferritic stainless steel material and the battery components formed using the ferritic stainless steel material is considered, the thickness of the ferritic stainless steel material is more preferably 0.1 mm or more. Furthermore, if the fire resistance and cost of the ferritic stainless steel material and the battery components formed using the ferritic stainless steel material are considered, the thickness of the ferritic stainless steel material is further preferably 0.2 to 0.8 mm. Furthermore, if the weldability of the ferritic stainless steel material and the battery components formed using the ferritic stainless steel material is considered, the thickness of the ferritic stainless steel material is further preferably 0.3 to 0.6 mm.
[0107] The ferritic stainless steel material of the embodiment of the present invention controls the composition and the amount of the prescribed precipitates as described above, so it has excellent impact absorption characteristics and high temperature rigidity during high-speed deformation. Therefore, the ferritic stainless steel material of the embodiment of the present invention has excellent battery protection performance and resistance to thermal runaway when the battery is impacted by a collision accident, etc. In addition, in order to suppress the thermal runaway of the battery caused by the impact, the formation of an insulating layer and the application of mica are required in the prior art, but these are not required for the ferritic stainless steel material of the embodiment of the present invention, so it helps to reduce the cost of battery components. That is, by using the ferritic stainless steel material of the embodiment of the present invention as a material for battery components of transportation equipment (especially automobiles, buses, railway vehicles, etc.), it is possible to seek environmental countermeasures based on lightweighting, improved collision safety, countermeasures against thermal runaway, and low cost.
[0108] (2) Method for manufacturing ferritic stainless steel material for battery components
[0109] The method for producing the ferritic stainless steel material according to the embodiment of the present invention is not particularly limited as long as it is a method that can produce a ferritic stainless steel material having the above-mentioned characteristics.
[0110] For example, the method for manufacturing a ferritic stainless steel material according to an embodiment of the present invention can be performed by annealing a cold-rolled material having the above composition at a temperature of 850 to 1050°C, and then cooling the material at a cooling rate of 10°C / second or less until 800°C. By controlling the conditions to be such, a ferritic stainless steel material having the above characteristics can be manufactured. Furthermore, after annealing and cooling as described above, pickling treatment can be performed as needed.
[0111] The above-mentioned production method will be described in detail below.
[0112] Cold rolled material can be manufactured by conventional methods. Specifically, first, the hot rolled material is obtained by melting the stainless steel having the above composition and forging or casting, and then hot rolling. Then, the hot rolled material is annealed, pickled and cold rolled in sequence to obtain the cold rolled material. Here, each process can be implemented using existing equipment, and the conditions can be appropriately adjusted according to the composition of the stainless steel, etc., without special restrictions. In addition, existing treatments (for example, surface grinding, temper rolling, treatment using a tension straightening machine, etc.) can also be performed as needed.
[0113] The cold rolled material obtained as described above is annealed at a temperature of 850 to 1050°C. By annealing in such a temperature range, a recrystallized structure can be obtained. In particular, from the viewpoint of workability and toughness, the annealing temperature is preferably 880 to 1000°C. By annealing in such a temperature range, the grain size number specified in JIS G0551:2013 can be controlled to 5 to 9, preferably 6 to 8. Furthermore, annealing can be implemented in a conventional annealing device, such as a continuous annealing line.
[0114] The cold-rolled material after annealing is usually cooled by air cooling, but in order to generate more than 0.010 volume % of Ti-based precipitates and / or Nb-based precipitates (hereinafter referred to as "precipitates") during the cooling process, the cooling rate until 800°C is set to 10°C / second or less. By cooling under such conditions, the precipitation of precipitates can be promoted. The lower limit of the cooling rate is not particularly limited, but if it is too slow, the precipitates are sometimes too coarse and the toughness is deteriorated. Therefore, it is preferred that the lower limit of the cooling rate is set to 3°C / second. In addition, if the productivity and the shape of the steel are considered, the cooling rate is more preferably 4 to 8°C / second.
[0115] The cold-rolled material after annealing cooled to 800°C is preferably cooled at a cooling rate of more than 10°C / second until 400°C (i.e., a temperature range from 800°C to 400°C), more preferably at 12°C / second or more, and further preferably at 15°C / second or more. This is because if the cooling rate is less than 10°C / second within this temperature range, intermetallic compounds such as Laves phase and σ phase are generated, which significantly reduce the low-temperature toughness. The upper limit of the cooling rate is not particularly limited, but if it is too fast, the shape of the steel material sometimes deteriorates significantly. Therefore, it is preferred to set the upper limit of the cooling rate to 100°C / second. In addition, if the pickling property and the shape of the steel material in the subsequent process are considered, the cooling rate is particularly preferably 20 to 80°C / second.
[0116] (3) Battery components
[0117] The battery component of the embodiment of the present invention comprises the above-mentioned ferritic stainless steel material. Since the above-mentioned ferritic stainless steel material has excellent impact absorption characteristics during high-speed deformation and high-temperature rigidity, the battery component has excellent battery protection performance and resistance to thermal runaway when the battery is impacted by a collision accident or the like.
[0118] The battery component is not particularly limited, and examples thereof include a battery case, a battery pack, a battery module, and a battery cover.
[0119] Example
[0120] The present invention will be described in detail below with reference to examples, but the present invention is not to be construed as being limited to these examples.
[0121] A ferritic stainless steel plate was produced according to the following procedure.
[0122] Stainless steel having the composition shown in Table 1 and Table 2 was melted, hot-rolled to obtain a hot-rolled plate with a thickness of 3.8 mm, and then pickled to obtain a hot-rolled pickled plate. Next, the hot-rolled pickled plate was cold-rolled to obtain a cold-rolled plate with a thickness of 0.6 mm. Next, the cold-rolled plate was annealed and cooled under the conditions shown in Table 3 and Table 4, and then pickled to obtain a cold-rolled annealed plate (ferritic stainless steel plate).
[0123] Table 1
[0124]
[0125] Table 2
[0126]
[0127] Table 3
[0128]
[0129] Table 4
[0130]
[0131] The cold rolled annealed sheets obtained as described above were evaluated as follows.
[0132] <Amount of Ti-based precipitates and / or Nb-based precipitates (hereinafter referred to simply as "precipitates")>
[0133] According to the point method specified in JIS G0555:2003, the cross section of the cold-rolled annealed sheet was observed under a microscope, and the amount of precipitates was calculated based on the area ratio of the precipitate existence area in the entire structure. Specifically, the resin was embedded in a manner that the cross section in the thickness direction parallel to the rolling direction of the cold-rolled annealed sheet became the observation surface, and after mirror polishing, the inclusions in 1 / 4 to 3 / 4 of the thickness were observed using an optical microscope at a magnification of 400 times. At this time, an optical microscope with a measuring lens having a 20×20 grid was used to observe 60 fields of view, and the area ratio was calculated by calculating the inclusions falling into the grid, which was used as the amount of precipitates (volume %).
[0134] <Particle size of precipitate>
[0135] Regarding the particle size of the precipitate, resin embedding is implemented in a manner that the thickness direction section parallel to the rolling direction of the cold-rolled annealed sheet becomes the observation surface, and after mirror polishing, the precipitate in 1 / 4 to 3 / 4 of the thickness is observed using a scanning electron microscope at a magnification of 3000 times. The observation is carried out in 10 fields of view, the area of the largest precipitate is calculated, and the equivalent circle diameter is obtained as the particle size of the precipitate. Furthermore, the precipitate is subjected to EDS analysis attached to the scanning electron microscope, and when the content of Ti and / or Nb in the precipitate is greater than the content of Ti and / or Nb in the base material, it is judged to be a precipitate.
[0136] <10 3 Flow stress at 10% strain during tensile test at a strain rate of / sec>
[0137] Tensile specimens with a parallel width of 2.0 mm and a line spacing of 4.8 mm were prepared from the cold-rolled annealed sheet in such a way that the tensile direction was the rolling direction, and a high-speed tensile test was performed. The high-speed tensile test was performed using a high-speed tensile tester (a high-speed tensile tester with a force gauge manufactured by Saginomiya Seisakusho Co., Ltd.) with a strain rate of 10 3 / second to determine the relationship between flow stress and strain. Then, the flow stress at 10% strain was determined.
[0138] <Young's modulus at 900℃>
[0139] The Young's modulus at 900°C was determined by the resonance method according to the method specified in JIS Z2280: 1993. Specifically, a sample for measurement with a length of 60 mm in the rolling direction and 10 mm in the width direction was prepared from the cold-rolled annealed sheet, and the sample was measured by the resonance method at 900°C using an elastic modulus measuring device (EG-HT elastic modulus measuring device manufactured by Nippon Technoplastics Co., Ltd.).
[0140] <Elongation at break at room temperature>
[0141] The tensile strength can be determined by conducting a tensile test at room temperature (25° C.) using a JIS No. 13 B test piece obtained from a cold-rolled annealed sheet in such a manner that the rolling direction is parallel to the parallel portion, using a tensile testing machine (Autograph AG-X, a precision universal testing machine manufactured by Shimadzu Corporation) in accordance with JIS Z2241:2011.
[0142] <Corrosion resistance (maximum pitting depth)>
[0143] A test piece with a rolling direction length of 150 mm and a width direction of 75 mm was prepared from the cold-rolled annealed sheet. Next, 30 cycles of JASO-CCT test were carried out (according to the conditions of M609-91, salt water spray (35°C, concentration 5%, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours) were regarded as 1 cycle), and then rust removal was carried out. Next, the maximum pitting depth was determined by the depth of focus method using a microscope. In this evaluation, the test piece with a maximum pitting depth of less than 200 μm was evaluated as ○, and the test piece with a maximum pitting depth of more than 200 μm was evaluated as ×.
[0144] The above-mentioned evaluation results are shown in Tables 5 and 6.
[0145] Table 5
[0146]
[0147] Table 6
[0148] As shown in Table 5, the cold-rolled annealed sheets of Examples 1 to 24 were 10 3 The flow stress at 10% strain and the Young's modulus at 900°C when the tensile test was performed at a strain rate of 1 / s were both high, and the impact absorption characteristics and high-temperature rigidity during high-speed deformation were excellent. In addition, the cold-rolled annealed sheets of Examples 1 to 24 also had good results for elongation at break and corrosion resistance (maximum pitting depth) at room temperature, and also had excellent workability and corrosion resistance.
[0149] On the other hand, as shown in Table 6, the cold-rolled annealed sheets of Comparative Examples 1 to 4 had inappropriate annealing temperature and cooling rate conditions and too little precipitate. 3 When the tensile test was conducted at a strain rate of 10 / sec, one or both of the flow stress at 10% strain and the Young's modulus at 900°C were reduced. In addition, the cold-rolled annealed sheets of Comparative Examples 5 to 31 did not satisfy the prescribed composition, and the annealing temperature was inappropriate in some of the comparative examples. 3When the tensile test was conducted at a strain rate of 10 / sec, one or both of the flow stress at 10% strain and the Young's modulus at 900°C were reduced. In addition, the cold-rolled annealed sheets of Comparative Examples 3 to 31 were also insufficient in one or both of the elongation at break and the corrosion resistance (maximum pitting depth) at room temperature.
[0150] As is apparent from the above results, the present invention can provide a ferritic stainless steel material for battery components, a method for producing the same, and a battery component that are excellent in battery protection performance and resistance to thermal runaway when an impact is applied to the battery due to a collision accident or the like.
[0151] In addition, based on the above results, the present invention can be implemented in the following aspects.
[0152] [1] A ferritic stainless steel material for battery components,
[0153] The invention has the following composition: containing, by mass, 0.001 to 0.050% C, 0.01 to 2.00% Si, 0.01 to 2.00% Mn, 0.010 to 0.050% P, 0.0001 to 0.0100% S, 10.0 to 30.0% Cr, 0.001 to 0.050% N, and further containing one or two selected from 0.01 to 0.50% Ti and 0.01 to 0.60% Nb, with the balance being Fe and impurities,
[0154] It contains 0.010 volume % or more of Ti-based precipitates and / or Nb-based precipitates.
[0155] [2] The ferritic stainless steel material for battery components according to [1],
[0156] The present invention further contains, on a mass basis, Ni: 0.01-2.00%, Al: 0.001-1.000%, Cu: 0.01-2.00%, Mo: 0.01-3.00%, V: 0.01-0.50%, Zr: 0.01-0.50%, B: 0.0002-0.0050%, Ca: 0.0005-0.0100%, W: 0.10-3.00%, Sn: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Ni: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Zr: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Zr: 0.0005-0.005 ... .01~0.50%, Co: 0.03~0.30%, Mg: 0.0002~0.0100%, Sb: 0.005~0.300%, REM: 0.002~0.200%, Ga: 0.0002~0.3000%, Ta: 0.001~1.000%, Hf: 0.001~1.000%, Bi: 0.001~0.020% or more.
[0157] [3] The ferritic stainless steel material for battery components according to [1] or [2],
[0158] The particle size of the Ti-based precipitates and / or the Nb-based precipitates is 10 μm or less.
[0159] [4] The ferritic stainless steel material for battery components according to any one of [1] to [3],
[0160] Take 10 3 The flow stress at 10% strain in a tensile test conducted at a strain rate of / sec is 500MPa or more, and
[0161] The Young's modulus at 900° C. is 80 GPa or more.
[0162] [5] The ferritic stainless steel material for battery components according to any one of [1] to [4],
[0163] Satisfy one or more of the following characteristics:
[0164] (1) The elongation at break at room temperature is more than 30%;
[0165] (2) The maximum pitting depth is less than 200 μm.
[0166] [6] The ferritic stainless steel material for battery components according to any one of [1] to [5],
[0167] The thickness is 1.0 mm or less.
[0168] [7] A method for producing a ferritic stainless steel material for battery components,
[0169] After annealing the cold-rolled material at a temperature of 850 to 1050°C, the cold-rolled material is cooled at a cooling rate of 10°C / second or less until 800°C, wherein the cold-rolled material has the following composition: on a mass basis, containing C: 0.001 to 0.050%, Si: 0.01 to 2.00%, Mn: 0.01 to 2.00%, P: 0.010 to 0.050%, S: 0.0001 to 0.0100%, Cr: 10.0 to 30.0%, N: 0.001 to 0.050%, and further containing one or two selected from Ti: 0.01 to 0.50% and Nb: 0.01 to 0.60%, with the balance being Fe and impurities.
[0170] [8] The method for producing a ferritic stainless steel material for battery components according to [7],
[0171] The cold-rolled material further contains, by mass, 0.01-2.00% Ni, 0.001-1.000% Al, 0.01-2.00% Cu, 0.01-3.00% Mo, 0.01-0.50% V, 0.01-0.50% Zr, 0.0002-0.0050% B, 0.0005-0.0100% Ca, 0.10-3.00% W, Sn : 0.01~0.50%, Co: 0.03~0.30%, Mg: 0.0002~0.0100%, Sb: 0.005~0.300%, REM: 0.002~0.200%, Ga: 0.0002~0.3000%, Ta: 0.001~1.000%, Hf: 0.001~1.000%, Bi: 0.001~0.020% or more.
[0172] [9] The method for producing a ferritic stainless steel material for battery components according to [7] or [8],
[0173] In the cooling, the cooling rate from 800° C. to 400° C. is set to exceed 10° C. / sec.
[0174]
[10] The method for producing a ferritic stainless steel material for battery components according to [9],
[0175] The cooling rate from 800° C. to 400° C. is 12° C. / sec or more.
[0176]
[11] A battery component comprising the ferritic stainless steel material for a battery component according to any one of [1] to [6].
Claims
1. A ferritic stainless steel material for battery components, The invention has the following composition: containing, by mass, 0.001 to 0.050% C, 0.01 to 2.00% Si, 0.01 to 2.00% Mn, 0.010 to 0.050% P, 0.0001 to 0.0100% S, 10.0 to 30.0% Cr, 0.001 to 0.050% N, and further containing one or two selected from 0.01 to 0.50% Ti and 0.01 to 0.60% Nb, with the balance being Fe and impurities, It contains 0.010 volume % or more of Ti-based precipitates and / or Nb-based precipitates.
2. The ferritic stainless steel material for battery components according to claim 1, The present invention further contains, on a mass basis, Ni: 0.01-2.00%, Al: 0.001-1.000%, Cu: 0.01-2.00%, Mo: 0.01-3.00%, V: 0.01-0.50%, Zr: 0.01-0.50%, B: 0.0002-0.0050%, Ca: 0.0005-0.0100%, W: 0.10-3.00%, Sn: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Ni: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Zr: 0.0002-0.0050%, Zr: 0.0005-0.0100%, Zr: 0.0005-0.005 ... .01~0.50%, Co: 0.03~0.30%, Mg: 0.0002~0.0100%, Sb: 0.005~0.300%, REM: 0.002~0.200%, Ga: 0.0002~0.3000%, Ta: 0.001~1.000%, Hf: 0.001~1.000%, Bi: 0.001~0.020% or more.
3. The ferritic stainless steel material for battery components according to claim 1 or 2, The particle size of the Ti-based precipitates and / or the Nb-based precipitates is 10 μm or less.
4. The ferritic stainless steel material for battery components according to any one of claims 1 to 3, Take 10 3 The flow stress at 10% strain in a tensile test conducted at a strain rate of / sec is 500MPa or more, and The Young's modulus at 900° C. is 80 GPa or more.
5. The ferritic stainless steel material for battery components according to any one of claims 1 to 4, Satisfy one or more of the following characteristics: (1) The elongation at break at room temperature is more than 30%; (2) The maximum pitting depth is less than 200 μm.
6. The ferritic stainless steel material for battery components according to any one of claims 1 to 5, The thickness is 1.0 mm or less.
7. A method for producing a ferritic stainless steel material for battery components, After annealing the cold-rolled material at a temperature of 850 to 1050°C, the cold-rolled material is cooled at a cooling rate of 10°C / second or less until 800°C, wherein the cold-rolled material has the following composition: on a mass basis, containing C: 0.001 to 0.050%, Si: 0.01 to 2.00%, Mn: 0.01 to 2.00%, P: 0.010 to 0.050%, S: 0.0001 to 0.0100%, Cr: 10.0 to 30.0%, N: 0.001 to 0.050%, and further containing one or two selected from Ti: 0.01 to 0.50% and Nb: 0.01 to 0.60%, with the balance being Fe and impurities.
8. The method for producing a ferritic stainless steel material for battery components according to claim 7, The cold-rolled material further contains, by mass, 0.01-2.00% Ni, 0.001-1.000% Al, 0.01-2.00% Cu, 0.01-3.00% Mo, 0.01-0.50% V, 0.01-0.50% Zr, 0.0002-0.0050% B, 0.0005-0.0100% Ca, 0.10-3.00% W, Sn : 0.01~0.50%, Co: 0.03~0.30%, Mg: 0.0002~0.0100%, Sb: 0.005~0.300%, REM: 0.002~0.200%, Ga: 0.0002~0.3000%, Ta: 0.001~1.000%, Hf: 0.001~1.000%, Bi: 0.001~0.020% or more. 9 . The method for producing a ferritic stainless steel material for a battery component according to claim 7 , wherein in the cooling, a cooling rate from 800° C. to 400° C. is set to exceed 10° C. / sec.
10. The method for producing a ferritic stainless steel material for battery components according to claim 9, The cooling rate from 800° C. to 400° C. is 12° C. / sec or more. 11 . A battery component comprising the ferritic stainless steel material for a battery component according to claim 1 .
Citation Information
Patent Citations
Treatment of gas and the like
CA500100A
Cooling apparatus for engine with exhaust turbocharger
JP1985090923A
Battery case mounted on electric car
JP1998188922A
Ferritic stainless steel for battery component member
JP2009167486A
Protective plate, battery cell assembly, battery module, and vehicle
JP2022522369A